KOMPOSISI JUMLAH DAN UKURAN PANJANG IKAN CAKALANG DAN TONGKOL HASIL TANGKAPAN PAYANG DI PERAIRAN PALABUHANRATU DAN BINUANGEUN - Domu Simbolon (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Palabuhanratuand Binuangeun waters are the central of potential fish catching activities in West Java and Banten Province. Fish resources which have important economic value from these waters are skipjack and frigate mackerel. Exploitation of these fish resources will be higher in future because demand of market from Jakarta tend to increase. The objective of this study is to know the amount and length size composition of skipjackand frigate mackerel cought by “payang” (surrounding net). The research method in this study was survey method through experimental fishing. The fish length composition of frigate mackerel cought in Binuangeun waters on period of March-May 2008 were dominated by large fish (65%), with the higher productivity found on May (482 kg/setting). Frigate mackerel cought in Palabuhanratu waters on period of March-May 2007 were dominated by small fish (73%), with the higher prouctivity on April (701 kg/setting). Moreover, skipjack catches in Palabuhanratu waters on period of Agust-October 2007 were dominated by small fish (71%), with the higher productivity on September (15,555 kg/vessel).Keywords : catch composition, skipjack, frigate mackerel, payang, Benuangeun, Palabuhanratu